Effect of S-glass Fibre and Nanoclay on the Tensile Properties of Epoxy Composites: A Comparative Study (Lafia Journal of Scientific and Industrial Research, 2025)
In this research work, the effect of S-glass fibre and nanoclay loading on the tensile properties of epoxy material are comparatively studied. Two groups of composites were fabricated, glass fibre/epoxy composites A, B, C, D, E, and F, which contains 0, 10, 20, 30, 40 and 50 wt.% S-glass fibre reinforcements respectively and nanoclay/epoxy composites A, B, C, D, E, and F with 0, 1, 2, 3, 4, and 5 wt.% nanoclay content, respectively. Tensile property of the all the composites fabricated were analysed and findings reported. Glass fibre/epoxy composite E, which contains 60 wt.% epoxy, 40 wt.% glass fibre was found to be the overall best performing composite. It possesses the following qualities: 98.93 MPa tensile strength, 1336.90 MPa tensile modulus and 0.072 strain at break whereas the best result on the tensile properties for nanoclay/epoxy group composites was obtained from composite E, which contains 4 wt.% nanoclay and 96 wt.% epoxy. It has the following behaviour; 60.837 MPa tensile strength, 845.00 MPa tensile modulus and 0.072 strain at break. The composite fabricated are suitable for wide range of applications such as aerospace industry for aircraft panel and body parts, marine for ship and vessels body parts, automobile industry for car bumper and body parts and civil engineering or structural engineering for high rise building frames etc.
Keywords: Composite; S-Glass Fibre; Nanoclay; Epoxy; Mechanical Properties